Hydrothermal Synthesis of Mordenite Type Zeolite - ANAS BOUSSAA, Sabiha; NIBOU, Djamel; BENFADEL, Karima; TALBI, Lamia; BOUKEZZATA, Assia; OUADAH, Yahia; ALLAM, Djaouida; KACİ, Samira (International Journal of Computational and Experimental Science and Engineering, 2023)
Zeolite is a crystalline alumino-silicate microporous material, which has been widely used as ion-exchangers, adsorbent and catalyst. Recently, several researches highlights the progress of zeolite-based catalysts in the CO2 conversion to valuable products. In the present work, hydrothermal synthesis of mordenite zeolite crystals, with composition of the chemical products Al2O3, 12.5 SiO2,2.4 NaOH, 110 H2O at 160°C for 96 hours (4 days) at Ph 11 is described. Results of characterization of the mordenite zeolite by XRD, FTIR, EDAX, SEM, TGA, are presented and discussed. In the present work, hydrothermal synthesis and characterization of mordenite zeolite crystals is described.